Study of indium tin oxide–MoS2 interface by atom probe tomography. (December 2019) - Ramos, Manuel; Nogan, John; Boll, Torben; Kauffmann-Weiss, Sandra; Rodriguez-Gonzalez, Claudia A.; Enriquez-Carrejo, Jose L.; Heilmaier, Martin
Abstract: Abstract : The molybdenum disulfide (MoS2 ) and indium tin oxide (ITO) interface were studied by atom probe tomography (APT). Raman spectroscopy, scanning electron microscopy, and grazing-incidence x-ray diffraction measurements were performed as complementary characterization. Results confirm that nanowires plated shape with the 〈110〉-orientation are aligned perpendicular to the ITO film with principal reflections at (002), (100), (101), (201), and Raman spectroscopy vibrational modes at E 1 2g at 378 cm −1 and A1g at 407 cm −1 correspond to 2H-MoS2 . APT reveals MoS +2, MoS +3 as predominant evaporated molecular ions on the sample, indicating no significant diffusion/segregation of Mo or S species within the ITO layer.